Advances in Radiotherapy for Glioblastoma - Mann, Justin; Ramakrishna, Rohan; Magge, Rajiv; Wernicke, A. Gabriella (Frontiers in Neurology, 2018)
External beam radiotherapy has long played a crucial role in the treatment of glioblastoma. Over the past several decades, significant advances in radiotherapy treatment and image guidance technology have led to enormous improvements in the ability to optimize definitive and salvage treatment. This review highlights several of the latest developments and controversies related to radiotherapy, including: the treatment of elderly patients, who continue to be a fragile and vulnerable population; potential salvage options for recurrent disease including reirradiation with chemotherapy; the latest imaging techniques allowing for more accurate and precise delineation of treatment volumes to maximize the therapeutic ratio of conformal radiotherapy; the ongoing preclinical and clinical data regarding the combination of immunotherapy with radiotherapy; the increasing evidence of cancer stem cell niches in the subventricular zone which may provide a potential target for local therapies. Lastly, continued development on many fronts have allowed for modestly improved outcomes while at the same time limiting toxicity.